2016
DOI: 10.18632/oncotarget.14080
|View full text |Cite
|
Sign up to set email alerts
|

Swimming attenuates inflammation, oxidative stress, and apoptosis in a rat model of dextran sulfate sodium-induced chronic colitis

Abstract: Increasing evidence suggests that regular physical exercise suppresses chronic inflammation. However, the potential inhibitory effects of swimming on dextran sulfate sodium (DSS)-induced chronic colitis, and its underlying mechanisms, remain unclear. In this study, rats were orally administered DSS to induce chronic colitis, and subsequently treated with or without swimming exercise. A 7-week swimming program (1 or 1.5 hours per day, 5 days per week) ameliorated DSS-caused colon shortening, colon barrier disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 49 publications
5
19
0
Order By: Relevance
“…Kim et al [ 18 ] also reported that BALB/c mice fed 4 weeks of western-style diet had increased inflammatory responses in conjunction with increased infiltration of macrophages into the colon, which were exacerbated by administration of DSS. With respect to exercise preconditioning, the current findings are consistent with previous studies reporting the therapeutic effects of exercise training against pathogenesis of experimentally-induced colitis models by suppressing pro-inflammatory responses and simultaneously stimulating anti-inflammatory responses [ 19 ] in conjunction with enhanced gut barrier function and symbiotic modifications in gut microbiota [ 11 ]. In addition, exercise training-induced enhancement of the immune system was observed in both animals [ 19 ] and humans [ 20 ] with exaggerated or chronic inflammation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Kim et al [ 18 ] also reported that BALB/c mice fed 4 weeks of western-style diet had increased inflammatory responses in conjunction with increased infiltration of macrophages into the colon, which were exacerbated by administration of DSS. With respect to exercise preconditioning, the current findings are consistent with previous studies reporting the therapeutic effects of exercise training against pathogenesis of experimentally-induced colitis models by suppressing pro-inflammatory responses and simultaneously stimulating anti-inflammatory responses [ 19 ] in conjunction with enhanced gut barrier function and symbiotic modifications in gut microbiota [ 11 ]. In addition, exercise training-induced enhancement of the immune system was observed in both animals [ 19 ] and humans [ 20 ] with exaggerated or chronic inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…With respect to exercise preconditioning, the current findings are consistent with previous studies reporting the therapeutic effects of exercise training against pathogenesis of experimentally-induced colitis models by suppressing pro-inflammatory responses and simultaneously stimulating anti-inflammatory responses [ 19 ] in conjunction with enhanced gut barrier function and symbiotic modifications in gut microbiota [ 11 ]. In addition, exercise training-induced enhancement of the immune system was observed in both animals [ 19 ] and humans [ 20 ] with exaggerated or chronic inflammation. In particular, exercise training-induced symbiotic modifications in gut microbiota have been found in animal models of inflammatory disease models, such as colon cancer and IBD [ 21 ], ulcerative colitis [ 22 ], HF-induced obesity [ 23 ], and sepsis [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…This has been reported in patients with UC, which suggested that the loss of epithelial cells in active UC was induced mainly by apoptosis in crypts of involved and adjacent uninvolved areas [ 52 ]. The same phenomenon also has been observed in CD patients [ 53 ] and murine models of colitis [ 54 ]. The key of keeping normal tissue homeostasis is to achieve balance of epithelial cell apoptosis and proliferation.…”
Section: Discussionsupporting
confidence: 76%
“…Also, the results of this study showed that interval training has a significant effect on the reduction of caspase-3 and increased cyclin-D in rats exposed to cadmium. Seven weeks of swimming training resulted in decreased activity of caspase-3, as well as apoptotic agents Bax and cytochrome C, and increased Bcl2 in rats (14). In this regard, it was reported that the Bax gene expression and the Bax ratio to Bcl2, which is a factor in the production of caspase-3, was reduced in the rats that ran twelve weeks on treadmill, compared to the control group, which did not exercise (15).…”
Section: Discussionmentioning
confidence: 95%